Comparison of Pica Prevalence Between Children and Adolescents with Iron Deficiency and Iron Deficiency Anaemia: A Prospective Cross-Sectional Study - Sadiye Sert; Şerife Karaçal Say (Genel Tıp Dergisi)

(untitled)
Background/Aims: The existing literature lacks comprehensive data on the association between the severity of iron deficiency (ID) and pica prevalence in children and adolescents. The aim of this study was to explore the prevalence of pica in apparently healthy children and adolescents, and by comparing its occurrence between those diagnosed with ID and those with IDA. Methods: This prospective cross-sectional study was conducted at the outpatient paediatric clinic over a period of three months. A total of 504 children and adolescents were enrolled in the study. Participants were categorized into three groups based on primary laboratory findings: Group 1 (healthy), Group 2 (isolated ID), and Group 3 (IDA). Results: A pica prevalence rate of 5.35% was observed, with a significantly higher occurrence among children suffering from IDA compared to those with ID and their healthy counterparts (p: <0.0001). Moreover, the prevalence was significantly higher in the 12-17.9 years age group (p: 0.01). Female sex and serum ferritin level emerged as the most significant independent predictors associated with pica in our investigation. Conclusions: Our study demonstrated a higher prevalence of the pica among children suffering from IDA, the most severe form of iron deficiencies, compared with those with isolated ID.